A longitudinal examination of rural status and suicide risk. Issue 4 (July 2015) - Neufeld, Eva; Hirdes, John P.; Perlman, Christopher M.; Rabinowitz, Terry
There is limited research on suicide risk in Canadian home care. Older adults have the highest rates of death by suicide worldwide. This article examines characteristics of rural and urban home care recipients with a hospital or emergency department visit for suicide attempts in Ontario, Canada. Factors that increase or decrease risk for emergent care are identified. This research builds on a growing need for health leadership to ensure that home care providers have appropriate training and resources to assess and respond to potential risk of suicide among frail elders.